2002
DOI: 10.2172/15010321
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vadose Zone Sediment: Borehole 299-E33-45 Near BX-102 in the B-BX-BY Waste Management Area

Abstract: Executive SummaryThis report was revised in September 2008 to remove acid-extractable sodium data from Table 4.22. The data was removed due to potential contamination introduced during the acid extraction process. The remaining text is unchanged from the original report issued in 2002.The overall goal of the Tank Farm Vadose Zone Project, led by CH2M HILL Hanford Group, Inc., is to define risks from past and future single-shell tank farm activities. To meet this goal, CH2M HILL Hanford Group, Inc., asked scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 15 publications
7
39
0
Order By: Relevance
“…This study demonstrated that calcium can significantly affect the rates of U(VI) dissolution, microbial reduction, and their coupling through aqueous U(VI) complexation reaction in bicarbonate solutions. Calcium is a common chemical component in groundwater and has a concentration range of 0.5-50 mmol/L and a medium of about 5 mmol/L in the Hanford porewater and groundwater (Serne et al, 2002). Speciation calculations and spectroscopic analyses indicated that either UO 2 (CO 3 ) 4À 3 or Ca 2 UO 2 (CO 3 ) 3 could dominate the aqueous U(VI) speciation depending on the chemical composition, pH, and calcium concentration in the Hanford pore and groundwaters (Dong et al, 2005;Wang et al, 2004).…”
Section: Implicationmentioning
confidence: 99%
“…This study demonstrated that calcium can significantly affect the rates of U(VI) dissolution, microbial reduction, and their coupling through aqueous U(VI) complexation reaction in bicarbonate solutions. Calcium is a common chemical component in groundwater and has a concentration range of 0.5-50 mmol/L and a medium of about 5 mmol/L in the Hanford porewater and groundwater (Serne et al, 2002). Speciation calculations and spectroscopic analyses indicated that either UO 2 (CO 3 ) 4À 3 or Ca 2 UO 2 (CO 3 ) 3 could dominate the aqueous U(VI) speciation depending on the chemical composition, pH, and calcium concentration in the Hanford pore and groundwaters (Dong et al, 2005;Wang et al, 2004).…”
Section: Implicationmentioning
confidence: 99%
“…This was the largest recorded single release of U(VI) to the subsurface at the Hanford site. Subsurface coring [ Serne et al , 2002] and U isotope analysis [ Christensen et al , 2004] revealed that the overfill event resulted in a large vadose plume that migrated to groundwater (250 m wide and 900 m long). Characterization of contaminated vadose zone sediments with X‐ray absorption spectroscopy, synchrotron X‐ray diffraction, laser induced fluorescence spectroscopy, and energy dispersive spectroscopy revealed that the sorbed uranium was hexavalent and precipitated as uranyl silicates, most likely as sodium boltwoodite [ Catalano et al , 2004; McKinley et al , 2006; Wang et al , 2005].…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations of uranium and silicon in the tank solution as well as those in contaminated and uncontaminated vadose zone sediments as determined via pore water analysis (7,8) are presented in Table 12. Uranium concentrations decrease from 10 -1 M in tank solutions to 1.910 -3 M in contaminated pore waters, but remain 10,000 times higher than background levels.…”
Section: The Hanford Vadose Zonementioning
confidence: 99%
“…Table 12. Uranyl and aqueous silica concentrations for solutions relevant to Hanford vadose zone sediments (7,8). The pH of uncontaminated groundwater, though unreported, is likely to be near neutral to mildly basic.…”
Section: The Hanford Vadose Zonementioning
confidence: 99%